Ontography Design for Children and Young Adults as a Knowledge Representation Tool: Relying on Re-engineering Methodology - azita malmir; Afshin Mousavi-chelak; soraya ziaei; Faeze Delghandi (Iranian Journal of Information Processing & Management)
The aim of the current research is to identify and draw the existing relationships between the concepts in the field of children and young adults and the design of the ontology using knowledge representation tools. In this research, the conceptual design of the ontology was done using the Methontology method, and based on the steps of this methodology its taxonomy structure was adapted from Dewey's Decimal Classification, and to extract the dictionary of words the entries of the ASKA thesaurus (Thesaurus of Kanoon-e Parvaresh-e Fekri Koodakan va Nojavanan) and children's subject headings have been used.  ISO 25964 standard was used in order to re-engineer the thesaurus and subject headings and turn them into the ontology. All thesaurus concepts and subject headings were considered as ontology classes and thesaurus terms as class labels. Definitions, domain notes, and other notes and information became descriptions. Hierarchical relations were considered as general hierarchical relations in ontology and were represented by subclass principle. Dependent relationships that indicate non-hierarchical relationships were defined by the researcher as semantic relationships between two concepts of ontology. The tool used for formalization, extracting the conceptual structure and coding and creating the ontology is Protégé software version 5.5.0. During the process of creating this ontology, the software outputs were evaluated by experts in the field. After identifying the basic concepts and the relationships between them, a conceptual structure was presented based on the findings of the previous two stages with an ontological approach. The results show that the ontology of children and young adults in thirteen main classes is formed and four types of Annotation Properties are used in it. This ontology includes 44 types of Object Properties and 20 types of data Properties and 305 examples. The formal and content validity of the conceptual structure of this ontology was confirmed by experts in the field of children and adolescents using the Delphi technique. In the ontology evaluation stage, in order to reject or confirm the authenticity of the work and the validity of the ontology, Felice's Kappa coefficient was used, and because in the five components of the research, Felice's kappa coefficient was almost a number close to 1, this indicates a greater agreement between the evaluators and shows that the ontology has good reliability. According to the findings of the research, it can be stated that children's thesaurus and subject headings are suitable tools for collecting ontological concepts and terms. Also, the ontology of children and young adults can be one of the useful and efficient tools of knowledge representation in this field. This essential tool can be a basis for the expansion and development of future terms and concepts of this field, and by using this ontology in knowledge-based systems, it is possible to improve retrieval systems, automatic reasoning processes, designing intelligent systems and knowledge engineering in the field of children and young adults.